Mechanical Water Pump Using Double Manifold Tank Hydram - Othman, Khairulnizam; Shamsuri, Muhammad Ameerul; Mohd Safi’e, Muhammad Aizzat; Irfan Iqbal Mohd Asri; Ngadimon, Khairulnizam; Hairul Mubarak Hassim (Multidisciplinary Applied Research and Innovation, 2021)
Abstract: It is difficult for farmers to get enough water in the sunny climater. It is a prototype that is used from ground water to dry soil, as a mechanical water pump. The problem statement generates ample pressure for the water to flow from underground to upper ground. The water flow from a spring or a trench into a pipe to create a pressure structure of the hydram principle. There is no additional energy required and the pump works indefinitely, as long as the flow of water decreases constantly. The material chosen for the pump depends on the application, the use of steel pipes is likely to result in the use of virgin polypropylene ( PP) or polyvinylidene fluoride ( PVDF), as a result of their low cost, strength and heat-resistance, pure water systems. The main aim of this study is to produce mechanical water pump components for a adequate supply of pressure for farmers. The supporting of pump systems requires a significant engineering, design, fabrication and erection effort.